An innovative tool for the evaluation of NOx emissions from road traffic - Boitor, Rozalia Melania; Cadar, Rodica Dorina; Maran, Petru Daniel; Petrelli, Marco (International Conference “Environmental Engineering”, 2020)
In the last years, there was great interest in the development of tools for an effective evaluation of road transport pollutant-related emissions, especially in the urban areas. This paper represents an innovative approach for identifying criticalities about pollutant emissions associated with road traffic and for defining effective policies in order to decrease pollutant emissions. The proposed tool concerns the development of an emission indicator, a proxy measure, which is useful for the assessment of emission problems, based on the use of GPS (Global Positioning System) instantaneous vehicle speed data. The tool can be considered an innovative and adequate solution in many cases in which the development of a valid and robust traffic simulation model, especially DTA (dynamic traffic assignment) is not available in the medium- and short-term horizon. The methodological process concerns the monitoring of road traffic conditions using GPS data from probe vehicles in combination with the use of GIS (Geographic Information System) for the estimation of an emission indicator. The tool has been tested on a real case study in the city of Cluj in Romania for the NOx emissions. The results show the utility of the tool in supporting policy and decision making, due to its ease of application and consistency, especially in defining critical areas.